Towards automatic mind maps generation of the Holy Quran : the case study of Surat al-Baqarah - Al-Salmi, Hamed Issa (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2021)
Nowadays, the need to employ a new technology to update, support education and enhance studying in general but specifically the Holy Quran is of great necessity. One of these new technologies that is often used is mind maps (mind mapping) as it has been used for decades in schools and colleges for note taking and learning. Even though mind maps are beneficial in terms of learning, creating maps after reading and understanding a text takes a long time. Mind maps were used in Holy Quran learning, but the majority of the learners use the traditional method of Quran memorization, which is based on repetition. The use of repetition in the process of memorization makes it difficult to memorize. Individuals require more time and they tend to forget what they have just memorized. In order to avoid these problems mentioned earlier, some researchers worked on creating mind maps of the Holy Quran and discussed the positive impact on using a manual drawn mind map in studying and memorizing the Holy Quran. Creating mind maps of one chapter of the Holy Quran took a long time. Researchers worked on automatic creation of mind maps for the English, Croatian and Indonesian languages but not for Arabic language. Based on the literature review of this research, there is no research emphasizing the creation of an automatic mind map of the Holy Quran. Therefore, the aim of this research is to develop an algorithm that automatically generates the topics based on the mind map of a set of verses in the Holy Quran. The general idea of the algorithm uses the frequency of the Arabic root word to find the topic of the verses. This work is significant because it will enhance the understanding and memorization of the Holy Quran by viewing the concepts in a way that is easy for the brain to perceive. Moreover, it could help extract new knowledge from the Holy Quran from the generated mind maps and facilitate the understanding of Tafsir. This research found the topics of all sets of verses based on the Topical Mushaf and Al-Duwayish mind map of Surat Al-Baqarah. The algorithm results were evaluated with topics of expert scholars and the error rate of the algorithm was 25% with the Topical Mushaf and about 35% with Al-Duwayish mind map topics. This work is limited to extract the topics from the Qur'anic verses as an input for the mind map drawing. This research contributes to the field of automatic generation of mind maps of the Holy Quran and provides the algorithm that automatically returns the topics of a set of Qur'anic verses.